P13 What to do in a syphilis outbreak. (18th May 2015) - Seppings, Louise; Tang, Alan; Chen, Fabian
Abstract : Background/introduction: In Autumn 2014 a surprising number of patients were being diagnosed with early syphilis, in the sexual health clinic, Reading. From January 2014 to January 2015 twenty-one early syphilis cases arose. Whereas 2013 totalled 5 cases, which was an average year. Aims/objectives: To identify if this constituted an outbreak. Determine why increasing numbers of early syphilis were arising and which patients groups were at risk. To prevent further cases. Methods: January to September cases were reviewed retrospectively and then new cases prospectively. Public Health England was notified and an action meeting ensued. Patient behaviours and contact tracing data collected. Letters written to inform healthcare services. Clinic information boards and website updated. Social media and appropriate charity organisations approached to reach target groups. Results: Eight presented with primary syphilis, ten with secondary and three with early latent. Eighteen cases were men who have sex with men (MSM), highlighting the main at risk group. Seven of the MSM were HIV positive with three being newly diagnosed. The average number of sexual contacts was twelve with one third using social networking apps to meet. Discussions/conclusions: Syphilis outbreak confirmed. MSM patients are the main risk group with one third HIV co-infection, which is a concern. Common usage of social networking apps identified to meet sexual partners, which can involve serosorting. Collaboration between sexual and Public Health teams resulted in raising awareness. Hopefully these measures will reduce the number of cases but it will require close monitoring.